Design Centric Attitude-Marketing Approach for Emerging Economies - D. R., Goodwin; K., Jyothsna Priyadarsini (Indian Journal of Marketing, 2009)
The symptomatic Indian malaise of a "chalta hai" attitude towards product design is a matter of concern. Why is it that in this exultant era of India shining we are yet to find Indian products that ravel design excellence? There are so many examples where attention to design details has fallen through the "not knowing and therefore not doing gap". Good product design should reflect an obsessive attention to detail. There's no point touting amorphous marketing promises on branding and identity of the final product doesn't reflect these in the actual customer experience. The recommendation is not to over-engineer the micro-architecture of every product- if the concept is to be a financial success, design has to balance issues of cost and profitability-but to avoid the very real danger of getting caught up in the seductive appeal of the Grand Idea at the cost for ignoring the myriad micro details that add up to a value-creating whole. Yes, innovation is about the big picture, the amazing new insight, the grand concept, but if the soul of the idea is not mirrored in the body of the product, then what you have is a promise that lacks integrity.